Platform development for control of induction machine (Part I hardware test rig) - Chen, Yun Xiang (2015)
In machine drive systems, direct current (DC) and alternating current (AC) motors are often used for speed control. Although the control of a DC motors is much simpler, AC motors are preferred due to their simple and reliable operations with ease of maintenance. Conventional methods of controlling an induction machine through variable speed control are widespread in many applications. However, in cases where the load changes are rampant in nature such as in the sea with changing currents, a more robust control over these dynamic conditions is required. Space vector control also known as field oriented control presents itself as an alternative solution over the conventional variable voltage/frequency scalar control. This project will be split into two parts. I will be designing and constructing a hardware test rig suitable for the testing of various control techniques. My partner Kang Jia Yi will be involved in the validation of control techniques before implementation on the test rig.